Rechargeable Aluminum-Ion Battery Based on MoS2Microsphere Cathode - Li, Z.; Niu, B.; Liu, Jian; Li, J.; Kang, F. (American Chemical Society, 2018)
© 2018 American Chemical Society. In recent years, a rechargeable aluminum-ion battery based on ionic liquid electrolyte is being extensively explored due to three-electron electrochemical reactions, rich resources, and safety. Herein, a rechargeable Al-ion battery composed of MoS2microsphere cathode, aluminum anode, and ionic liquid electrolyte has been fabricated for the first time. It can be found that Al3+intercalates into the MoS2during the electrochemical reaction, whereas the storage mechanisms of the electrode material interface and internal are quite different. This result is confirmed by ex situ X-ray photoelectron spectroscopy and X-ray diffraction etching techniques. Meanwhile, this aluminum-ion battery also shows excellent electrochemical performance, such as a discharge specific capacity of 253.6 mA h g-1at a current density of 20 mA g-1and a discharge capacity of 66.7 mA h g-1at a current density of 40 mA g-1after 100 cycles. This will lay a solid foundation for the commercialization of aluminum-ion batteries.